1992
DOI: 10.1016/0735-1097(92)90246-j
|View full text |Cite
|
Sign up to set email alerts
|

Excessive vasoconstriction in rheumatic mitral stenosis with modestly reduced ejection fraction

Abstract: Excessive vasoconstriction may account for the higher afterload, lower ejection performance and lower cardiac output observed in a subset of patients with mitral stenosis because contractile dysfunction could not be detected and left ventricular filling--which was not subnormal despite severe inflow obstruction--improved only modestly after valvuloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…14) could be explained by differences in body surface area (1.8 Ϯ 0.3 vs. 1.5 Ϯ 0.12 m 2 ). In our study, the 67-ml SV value was consistent with the 58-ml value previously reported (29,30). SV did not significantly change after BVM, as reported in some studies (7,19).…”
Section: Comparison With Previous Studiessupporting
confidence: 93%
See 3 more Smart Citations
“…14) could be explained by differences in body surface area (1.8 Ϯ 0.3 vs. 1.5 Ϯ 0.12 m 2 ). In our study, the 67-ml SV value was consistent with the 58-ml value previously reported (29,30). SV did not significantly change after BVM, as reported in some studies (7,19).…”
Section: Comparison With Previous Studiessupporting
confidence: 93%
“…SV did not significantly change after BVM, as reported in some studies (7,19). Others have reported that SV increased after BMV (14,29). These disparities may be related to differences in the incidence and severity of mitral regurgitation and atrial shunts after BMV.…”
Section: Comparison With Previous Studiesmentioning
confidence: 65%
See 2 more Smart Citations
“…valvuloplasty . This may be explained by one or more of the following mechanisms: increased afterload due to.excessive vasoconstriction [9], blood loss with decreased venous return, left to right were not estimated before and after dilatation. In contrast, the Inoue double-lumen catheter which was used in all of our patients has the advantage of a self-positioning mechanism (i.e., it anchors to the mitral valve during inflation), which avoids the slippage that may otherwise cause significant trauma to the endocardium during inflation.…”
Section: Discussionmentioning
confidence: 84%